2003
DOI: 10.12968/bjtr.2003.10.1.13581
|View full text |Cite
|
Sign up to set email alerts
|

Stressful expectations of junior occupational therapists: 2

Abstract: In the first article of this two-part series, the author reviewed the background literature on occupational stress and therapists' expectations of their work. This article develops this material by reporting a study that explored the interaction of these variables in a group of occupational therapists who qualified from St Loye's School of Health Studies in 2000.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
0
2
0
4
Order By: Relevance
“…Wright (2001) confirmed that new occupational therapists looked to consolidate their skills, feel confident in their role and have access to role models and supervision similar to that when a student. Younger staff arrive with higher expectations of practice than do their more mature peers and might be more stressed if these expectations are not met (Rugg 2003). The stress experienced by some newly qualified staff may be compounded because they are going through major life events, usually involving a change in location as well as new colleagues.…”
Section: Mary Morleymentioning
confidence: 99%
“…Wright (2001) confirmed that new occupational therapists looked to consolidate their skills, feel confident in their role and have access to role models and supervision similar to that when a student. Younger staff arrive with higher expectations of practice than do their more mature peers and might be more stressed if these expectations are not met (Rugg 2003). The stress experienced by some newly qualified staff may be compounded because they are going through major life events, usually involving a change in location as well as new colleagues.…”
Section: Mary Morleymentioning
confidence: 99%
“…Este estudo situa-se em um contexto específico de pesquisa sobre o exercício profissional e aprendizagem da prática para terapeutas ocupacionais (especialização em terapia ocupacional em saúde mental) e os dilemas e as construções encontradas indicam ressonância com resultados de outros estudos (Hunt, Kennedy-Jones, 2010;Morley, 2006;2007;Morley et al, 2007;Nayar et al, 2013;Rugg, 2003;Toal-Sullivan, 2006;Spalding, 2000;Mitchell, Unsworth, 2005;Lins, Matsukura, 2015;Mângia et al, 2010;Juns, Lancman, 2011).…”
Section: Discussionunclassified
“…Dificuldades com a identidade profissional são presentes no início da carreira (Hunt, Kennedy-Jones, 2010;Morley, 2006;2007;Morley et al, 2007;Nayar et al, 2013;Rugg, 2003;Toal-Sullivan, 2006), em profissionais mais experientes (Edwards, Dirette, 2010) e também no campo da saúde mental, caracterizando-se um importante fator estressor (Lloyd et al, 2007;Basset, Lloyd, 2001). Em nosso trabalho, esse dilema esteve ligado à tentativa de reconhecimento do que é específico da profissão no campo da saúde mental, inicialmente atrelado ao uso de atividades.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Previous literature has explored the challenges experienced by newly qualified occupational therapists (NQOTs) as they move into practice (Tryssenaar and Perkins 2001, Rugg 2003, Hodgetts et al 2007, Lloyd et al 2007. Morley (2007) reported a preceptorship programme to ease these challenges by seeking to support NQOTs during the transition, in order to facilitate the development of clinical skills and professional behaviour and to promote reflective practice.…”
Section: Introductionmentioning
confidence: 99%